2010
DOI: 10.1016/j.cbpb.2009.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of expression, activity and role in antibacterial immunity of Anopheles gambiae lysozyme c-1

Abstract: There are eight lysozyme genes in the Anopheles gambiae genome. Transcripts of one of these genes, LYSC-1, increased in Anopheles gambiae cell line 4a3B by 24 h after exposure to heat-killed Micrococcus luteus. Lysozyme activity was also identified in conditioned media from the cell line from which the protein was purified to homogeneity using ion exchange and gel filtration. Mass spectrometric analysis of the purified protein showed 100% identity to lysozyme c-1. Purified lysozyme c-1 was tested against non-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 59 publications
3
41
0
Order By: Relevance
“…Anopheles dirus A was reared under laboratory conditions in an insectary in an incubator set to 70–80% relative humidity and 25–27 °C at AFRIMS (Armed Forces Research Institute of Medical Sciences, Thailand) and at the Department of Entomology, University of Wisconsin- Madison, Wisconsin, USA according to previously described protocols (Paskewitz et al, 1999; Kajla et al, 2010 and 2011) with the modification that these mosquitoes were mated artificially.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anopheles dirus A was reared under laboratory conditions in an insectary in an incubator set to 70–80% relative humidity and 25–27 °C at AFRIMS (Armed Forces Research Institute of Medical Sciences, Thailand) and at the Department of Entomology, University of Wisconsin- Madison, Wisconsin, USA according to previously described protocols (Paskewitz et al, 1999; Kajla et al, 2010 and 2011) with the modification that these mosquitoes were mated artificially.…”
Section: Methodsmentioning
confidence: 99%
“…We have investigated a group of antimicrobial enzymes called lysozymes (Li et al, 2005; Li and Paskewitz, 2006; Paskewitz et al, 2008; Kajla et al, 2010). These enzymes are defined by the ability to hydrolyze the 1–4 glycosidic bonds between N-acetylglucosamine (NAG) and N-acetylmuramic acid (NAM) of the peptidoglycan (PGN) present in the cell walls of bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spodoptera eridania (Anderson & Cook, 1979), B. mori (Abraham et al, 1995) and Gryllus texensis (Adamo, 2004), and E. coli is also considered to be an effective inducer of insect humoral immune responses in general (Erler et al, 2011) and of hemolymph lysozyme activity, in particular, e.g. B. mori (Sumida et al, 1992;Abraham et al, 1995), Melanoplus sanguinipes (Gillespie et al, 1993), Artogeia rapae (Bang & Yoe, 2005), S. frugiperda (Chapelle et al, 2009) and Anopheles gambiae (Kajla et al, 2010). Also, there is no clear-cut specificity in terms of pathogen recognition, signaling pathways, or effector molecules in the course of induction of humoral responses in insects (Marmaras & Lamproulou, 2009).…”
Section: ± 1029mentioning
confidence: 99%
“…Concerning malaria, few studies have already shown the feasibility of approaches based on mosquito guts bacteria to deliver anti-Plasmodium effector molecules within the insect Jacobs-Lorena 2005, Riehle et al 2007). Many bacteria constitute the midgut microflora of some malaria vector mosquitoes (Dong et al 2009;Meister et al 2009;Kajla et al 2010) but, to date, the only stable association with a mosquito host is that described for bacteria of the genus Asaia (Favia et al 2007).…”
Section: Introductionmentioning
confidence: 99%